2001
DOI: 10.1016/s0002-9440(10)64077-1
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage-Derived Chemokine (MDC/CCL22) and CCR4 Are Involved in the Formation of T Lymphocyte-Dendritic Cell Clusters in Human Inflamed Skin and Secondary Lymphoid Tissue

Abstract: Chemokines are small secreted proteins that play critical roles in the migration of various types of leukocytes. Some chemokines are also likely to be involved in the interactions between T cells and dendritic cells (DC).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
72
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 94 publications
(78 citation statements)
references
References 30 publications
4
72
1
1
Order By: Relevance
“…Thus, even though the concentrations of CCL28 found free in saliva and milk are relatively low compared with its IC 50 for various microbes, its high surface concentrations on the mucosal surfaces together with synergistic effects with other antimicrobial factors rich in mucosal secretions (33) may provide a highly effective barrier protection against a wide spectrum of microbes. Notably, autologous skin flaps transplanted into the oral cavity to reconstruct large tissue defects after radical resection of oral cancer are known to be frequently infected with C. albicans (23). Skin surfaces, which may be less effectively covered by CCL28 than normal oral mucosa, may be easily colonized by C. albicans even in the presence of high concentrations of histatins and other antimicrobial agents in the saliva.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Thus, even though the concentrations of CCL28 found free in saliva and milk are relatively low compared with its IC 50 for various microbes, its high surface concentrations on the mucosal surfaces together with synergistic effects with other antimicrobial factors rich in mucosal secretions (33) may provide a highly effective barrier protection against a wide spectrum of microbes. Notably, autologous skin flaps transplanted into the oral cavity to reconstruct large tissue defects after radical resection of oral cancer are known to be frequently infected with C. albicans (23). Skin surfaces, which may be less effectively covered by CCL28 than normal oral mucosa, may be easily colonized by C. albicans even in the presence of high concentrations of histatins and other antimicrobial agents in the saliva.…”
Section: Discussionmentioning
confidence: 99%
“…Written informed consents were obtained from both patients. Immunohistochemistry was conducted as described previously (23). In brief, periodate-lysine-4% paraformaldehyde-prefixed frozen sections were reacted with mouse monoclonal anti-CCL28 (clone no.…”
Section: Immunohistochemistrymentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the expressions of IL-4, CCR4, and CCR8 may require allergen stimulation in the inflamed region. In addition, TARC and MDC are expressed not only in airway epithelium but also in the other organs such as skin (31,32) and the nose (33). Taken together, it is suggested that T cells in the peripheral blood, especially Th2-type cells, of asthmatic patients migrate from blood into bronchial tissue without inflammatory stimulation by a mechanism other than chemokines such as MDC and TARC and their ligands of CCR4.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, whether DCs can fully mature depends on their ability to undergo in vivo migration. The in vivo migration of DCs is a complicated and successive process in which a series of chemokines and accessory receptors play critical roles (29,30). Thus, we investigated the impact of CD40/CD40L costimulatory signal on the function of mDCs and DC-activated T cells as well as their chemokine secretion and chemokine receptor expression.…”
Section: Discussionmentioning
confidence: 99%